Dynamics of the HIV Gag Lattice Detected by Localization Correlation Analysis and Time-Lapse iPALM - Saha, Ipsita (Biophys J, 2020)
Immature human immunodeficiency virus (HIV) virions have a lattice of Gag and Gag-Pol proteins anchored to the lumen of their envelope. Using electron microscopy, we demonstrate that HIV virus-like particles (VLPs) assembled by the viral protein Gag and tagged at its C-terminus with the fluorescent protein Dendra2 have the same morphology and size as the VLPs assembled using only HIV Gag. We characterize the photophysical properties of Dendra2 and demonstrate that 60% of Dendra2 molecules can be photoswitched and reliably counted in our interferometric photoactivated localization microscopy (iPALM) setup. We further perform iPALM imaging on immobilized HIV Gag-Dendra2 VLPs and demonstrate that we can localize and count 900–1600 Dendra2 molecules within each immobilized VLP with a single-molecule localization precision better than (10 nm)(3). Our molecular counts correspond to 1400–2400 Gag-Dendra2 proteins incorporated within each VLP. We further calculate temporal correlation functions of localization data, which we present as localization correlation analysis, and show dynamics within the lattice of immobilized VLPs in the timescale of 10–100 s. We further use our localization data to reconstruct time-lapse iPALM images of the Gag-Dendra2 lattice within the lumen of immobilized VLPs. The iPALM time-lapse images show significant lattice dynamics within the lumen of VLPs. Addition of disuccinimidyl suberate to the VLPs completely abrogated these dynamics as observed in both localization correlation analysis and time-lapse iPALM. In a complementary approach, we utilized HaXS8 cross-linking reactions between Halo and SNAP proteins and verified lattice dynamics in purified VLPs incorporating 10% Gag-SNAP, 10% Gag-Halo, and 80% Gag proteins. The HIV Gag lattice, along with the structural lattice of other enveloped viruses, has been mostly considered static. Our study provides an important tool to investigate the dynamics within these enveloped viruses.